The effects of repeated backward running training on measures of physical fitness in youth male soccer players - Negra, Y.; Sammoud, S.; Ramirez-Campillo, R.; Moran, J.; Chaabene, H. (Journal of Sports Sciences, 2022)
This study explored the effects of an 8-week repeated backward running training (RBRT) programme on measures of physical fitness in youth male soccer players. Youth male soccer players were randomly allocated into a RBRT group (n = 20; 13.95 ± 0.22y) or a control group (CG; n = 16; 14.86 ± 0.29y). The CG continued normal soccer training, while the RBRT group replaced some soccer drills with RBRT twice per week. Within-group analysis revealed that RBRT improved all performance variables (?-9.99% to 14.50%; effect size [ES] = -1.79 to 1.29; p = 0.001). Meanwhile, trivial-to-moderate detrimental effects on sprinting and change of direction (CoD) speed (?1.55% to 10.40%; p = 0.05) were noted in the CG. The number of individuals improving performance above the smallest worthwhile change ranged from 65-100% across all performance variables in the RBRT group, whereas<50% in the CG reached that threshold. The between-group analysis indicated that the RBRT group improved performance on all performance tasks more than the CG (ES = -2.23 to 1.10; p = 0.05). These findings demonstrate that substituting part of a standard soccer training regimen with RBRT can enhance youth soccer players` sprinting, CoD, jumping, and RSA performance.